1975
DOI: 10.3189/s0022143000021948
|View full text |Cite
|
Sign up to set email alerts
|

Climatological, Implications of Microparticle Concentrations in the Ice Core From “Byrd” Station, Western Antarctica

Abstract: The concentration of microparticles in the 2 164 m long ice core from “Byrd” station Antarctica, varies cyclically. Highest concentrations of 0.65 μm diameter microparticles occur where oxygen-isotope studies show lowest paleotemperatures. The age of the bottom ice estimated from microparticle-concentration variations, assuming an annual cycle, is 27 000 years, much less than from oxygen-isotope studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…The detection of stable oxygen-isotope or micro particle variations (Johnsen and others, 1972;Thompson and others, 1975) requires that the snow of a particular season be present. The oxygen-isotope method may require, for example, that each summer snow layer be present.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of stable oxygen-isotope or micro particle variations (Johnsen and others, 1972;Thompson and others, 1975) requires that the snow of a particular season be present. The oxygen-isotope method may require, for example, that each summer snow layer be present.…”
Section: Discussionmentioning
confidence: 99%
“…by identification of total ~-activity reference horizons. This is undoubtedly what Thompson and others (1975) have in mind, when stating on p. 441: "In the 1973-74 Antarctic field season one of us (L.C.T.) collected samples for microparticle analysis from areas near 'Byrd' station where the snow stratigraphy and chronology are well known".…”
mentioning
confidence: 99%
“…We feel this problem should b e solved prior to discussing flow patterns or time scales based on any interpretation of dust profiles. It is true that there is some degree of similarity between the dust and 8( IB O ) variations in (according to Johnsen and others, 1972 ) a 15500 year old increm ent (Thompson and others, 1975, fig. I ), but it is difficult to accept as "strong presumptive evidence", because the 8 oscillation is short and obviously atypical, while the dust profile is disturbed by numerous volcanic ash bands.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, grain size and mineral composition of IM are often applied for source discrimination. Thompson et al [8] found that grain size distributions of IM can dis-tinguish the origin of regional and global dust. Studies on the mineral composition in Vostok ice cores suggested that southern Australia dust sources have been of major importance, indicating that the Vostok glacial areas might have been affected by air masses differently from other Antarctic regions [9].…”
mentioning
confidence: 99%